The Influence Of Emotional Intelligence And Digital Literacy On Teacher Performance - Arifin, Arifin; Yusuf, Yusuf (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of emotional intelligence and digital literacy on the performance of elementary school teachers in Pamulang District, South Tangerang. Using a quantitative method with a survey approach, data were collected from 80 teachers selected through purposive sampling. Data analysis was conducted using multiple linear regression with SPSS 26.00. The results indicate that emotional intelligence and digital literacy significantly influence teacher performance, with digital literacy having a more dominant impact than emotional intelligence. The coefficient of determination test shows that these two independent variables explain 56.4% of the variance in teacher performance, while the remaining 43.6% is influenced by other factors not analyzed in this study. Additionally, the F-test confirms that the regression model is statistically significant in explaining teacher performance. Therefore, improving digital literacy and emotional intelligence is crucial in enhancing teaching quality. Continuous training is necessary to strengthen teachers' digital skills and emotional management to address the challenges of education in the digital era.